PENGUATAN PEMAHAMAN PRODUK PANGAN AMAN DAN HALAL BAGI WARGA DESA BESUKI KECAMATAN LUMBIR KABUPATEN - Arinda Nur Cahyani; Febia Citraeni Rusdaita; Elsa Nurmala (STIKes Ibnu Sina Ajibarang, 2023)
Food safety and product halalness are important matters and must be fulfilled for both micro industry and macro scale industry producers. One area that has many MSMEs is Besuki Village, Lumbir Banyumas District. The purpose of this community service is to strengthen and increase understanding and knowledge in determining safe and halal food. The method of implementing this activity is the provision of material and discussions which are conducted offline at the Besuki Village Hall. This activity took place on March 18 2023. The evaluation was carried out by giving a pre-test and post-test. The average value between experiencing an increase and after giving the material